Neuraxial anesthesia for orthopedic surgery: systematic review and meta-analysis of randomized clinical trials - Barbosa, Fabiano Timbó (2013)
CONTEXT AND OBJECTIVE: Taking the outcome of mortality into consideration, there is controversy about the beneficial effects of neuraxial anesthesia for orthopedic surgery. The aim of this study was to compare the effectiveness and safety of neuraxial anesthesia versus general anesthesia for orthopedic surgery. DESIGN AND SETTING: Systematic review at Universidade Federal de Alagoas. METHODS: We searched the Cochrane Central Register of Controlled Trials (Issue 10, 2012), PubMed (1966 to November 2012), Lilacs (1982 to November 2012), SciELO, EMBASE (1974 to November 2012) and reference lists of the studies included. Only randomized controlled trials were included. RESULTS: Out of 5,032 titles and abstracts, 17 studies were included. There were no statistically significant differences in mortality (risk difference, RD: -0.01; 95% confidence interval, CI: -0.04 to 0.01; n = 1903), stroke (RD: 0.02; 95% CI: -0.04 to 0.08; n = 259), myocardial infarction (RD: -0.01; 95% CI: -0.04 to 0.02; n = 291), length of hospitalization (mean difference, -0.05; 95% CI: -0.69 to 0.58; n = 870), postoperative cognitive dysfunction (RD: 0.00; 95% CI: -0.04 to 0.05; n = 479) or pneumonia (odds ratio, 0.61; 95% CI: 0.25 to 1.49; n = 167). CONCLUSION: So far, the evidence available from the studies included is insufficient to prove that neuraxial anesthesia is more effective and safer than general anesthesia for orthopedic surgery. However, this systematic review does not rule out clinically important differences with regard to mortality, stroke, myocardial infarction, length of hospitalization, postoperative cognitive dysfunction or pneumonia.